THE EFFECT OF TOTAL QUALITY MANAGEMENT (TQM) ON MANAGERIAL PERFORMANCE AT PT. LOGAM PERKASA RETAILINDO - Kuncorosidi Kuncorosidi; Rangga Saka Pradana; Jojo Jojo (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2024)
In this study, PT. Logam Perkasa Retailindo, commonly known by most Subang people, is the Roma Building Shop, which is the unit of analysis. PT. Logam Perkasa Retailindo was chosen because it is a retail store that has been established for 2 years but is well known among the people of Subang in particular, however, with the development of the retail industry in Subang City, PT. Logam Perkasa Retailindo began to get competitors from retail shops selling the same building products. The research method used in this study is an explanatory survey, and the type of research used in this research is descriptive and verification using a quantitative approach. The population in this study are all employees of PT. Logam Perkasa Retailindo has as many as 55 employees. In this study, the sampling technique used was non-probability sampling. The type of sample used from non-probability sampling in this study is saturated sampling. The final results of this study prove that Total Quality Management (TQM) influences Managerial Performance at PT. Perkasa Retailindo partially. With this, the researchers suggest that PT.Logam Perkasa Retailindo can implement Total Quality Management (TQM) optimally, as well as carry out continuous evaluation and improvement so that it can continue to improve the quality of its resources, both products and services, and increase customer satisfaction, so that it can continue to compete with similar companies